Right upper quadrant cytoreductive procedures and cardiophrenic lymph node resection in primary debulkig surgery for ovarian cancer - Joao Casanova; José Filipe Cunha (Elsevier, 2021)
Upfront debulking surgery followed by adjuvant chemotherapy still remains as the mainstay approach to patients with advanced ovarian cancer (Eisenhauer et al., 2006).Upper abdominal surgery is often required to achieve complete gross resection and there are several studies in the literature reporting increased survival, as well as a minimal but acceptable increase in morbidity, as a result of this shift in the surgical paradigm (Chi et al., 2009).Cardiophrenic lymph nodes (CPLNs), also referred to as paracardiac and supradiaphragmatic lymph nodes, are located just above the diaphragm. In diseases such as advanced ovarian cancer, where there is often considerable abdominal and peritoneal tumor burden, these lymph nodes can harbor metastases. These nodes are usually larger than 5 mm in diameter and are easily identified on computed tomography.Evidence suggests that this finding should not preclude primary debulking surgery (if resectable disease in the abdomen) as it is associated with an increased median overall survival even in stage IV disease (Cowan et al., 2017; Prader et al., 2016).We present a video highlighting one of the most commonly performed debulking procedures in the upper abdomen - right diaphragmatic peritoneal stripping (the patient had multiple small implants in both the diaphragmatic peritoneum and Morisońs Pouch peritoneum, so en bloc resection was performed) - followed by a transabdominal excision of an enlarged right cardiophrenic lymph node. The defect was closed with a 2-0 polypropylene running suture.